Association of serum reproductive hormones changes after neoadjuvant chemotherapy with hormone receptors expression alterations and survival outcomes in breast cancer - Lan, Ailin; Jin, Yudi; Wang, Yu; Ding, Nan; Wang, Yihua; Dai, Yuran; Jiang, Linshan; Tang, Zhenrong; Peng, Yang; Liu, Shengchun (Frontiers in Surgery, 2022)
Purpose This study aimed to determine the effect of neoadjuvant chemotherapy (NAC) on circulating levels of reproductive hormones and evaluate the correlation of hormones changes after NAC with hormone receptors expression alterations and relapse-free survival (RFS) outcomes in breast cancer. Methods Information from 181 breast cancer patients who received NAC were retrospectively analyzed. For hormones parameters, the median and interquartile range (IQR) were provided at baseline and at the end of NAC, then were compared by Wilcoxon signed-rank test. Categorical variables were represented as numbers and percentages and were compared via two-sided chi-square and Fisher’s tests. The RFS outcomes were compared between patients according to hormones changes using the log-rank test. Univariate and multivariate survival analyses with hazard ratios (HR) and 95% confidence intervals (95% CI) were carried out using Cox regression. Results Sex steroids including estradiol, progesterone, testosterone and dehydroepiandrosterone sulfate (DHEAS) levels decreased significantly after NAC among both premenopausal and postmenopausal patients (all P < 0.05). Decreased estradiol levels were associated with reduced progesterone receptor (PR) expression (P = 0.030). In multivariate survival analysis, the non-decreased progesterone level was strongly associated with worse RFS (non-decreased vs decreased, HR = 7.178, 95% CI 2.340-22.019, P = 0.001). Patients with decreased progesterone levels exhibited better 3-year RFS compared with those with non-decreased (87.6% vs 58.3%, log-rank, P = 0.001). Conclusion Multiple reproductive hormones levels were influenced by NAC. The change of estradiol level had a positive connection with PR expression alteration. Furthermore, the negative correlation between the change of progesterone level and RFS outcomes was found. These findings may provide a theoretical basis for pre-operative endocrine therapy combined with NAC in breast cancer patients.